Can you see what I see? : picture puzzles to search and solve - Wick, Walter (New York : Scholastic, 2002)
Presents twelve brain-teasing hidden picture puzzles to solve.
"Cartwheel books"--T.p. verso.
Pub Weekly
Kirkus Review
3.9
K-3
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Picture puzzles